Statistical evaluation ff physical and chemical characteristics of effluent at a university (Research, Society and Development, 2023)
The aim of this study is to characterize the physic-chemical aspects of the effluent generated at a university campus and statistically analysing how the effluent characteristics are affected by campus activities. Effluent samples were done along one year. Parameters analysed were: COD, total solids, suspended solids, dissolved solids, chloride, pH, ammoniacal nitrogen, conductivity and flow rate of the effluent based on water consumption. Statistical studies were carried out in order to analyse the impacts of campus activities on effluent quality parameters. It was observed that chemical oxygen demand (COD) and dissolved solids vary according to the days of the week, whereas pH, chloride and conductivity do not. However, none of these parameters have statistically different average values throughout the hours of the day. Furthermore, there are no differences between the average pH values of the term and pH of the vacation period; instead, COD, chloride and conductivity have statistically lower average values in the vacation period. Correlation tests have shown that the academic population does not directly influence pH and concentrations of COD, total solids and suspended solids. In addition, it was concluded that the number of served meals can influence effluent characteristics. This work shows that campus effluent has unique characteristics. All data and analysis of this work can support better projects and management of sewage treatment systems in educational institutions. Studies on the broad characterization of university effluents are scarce in the literature. This work aims to complement the literature on this topic.